Structural behaviour of cracked Pre-Tensioned (PRT) concrete beam under vertical static load / Nurul Huda Suliman - Suliman, Nurul Huda (2019)
Retrofitting of concrete elements is one of the methods among numerous other methods in extending the lifespan of the structural members without undergoing the process of redesigning and reconstructing. At a certain occasion, concrete structural members are exposed to harm without a proper maintenance which could eventually lead to structural failures. Hence to avoid, there are various types of repairing tools, materials and techniques have been developed over time depending on type of damages and how severe the damages are. In this study however, was specifically chosen a retrofitting approach by installing Carbon Fiber Reinforced Polymer (CFRP) sheets and plates on the surface of a cracked structural member of beam with the help of epoxy to adhere them and producing new composites. The CFRP is commonly known as lightweight material that produces higher tensile strength compared to mild steel. In ensuring that, this study has been decided to research on how effective does the CFRP is in the form of sheets and plates towards a cracked beam. In addition to that, as common practices in Malaysia is lack on early diagnose towards repair works, this study has purposely runs on a delayed timeframe with taking measure of the pre-crack size which considering on first visible crack and direct apply the CFRP retrofit. The effectiveness of this method were measured through Load-Displacement Relationship between controlled specimen and the retrofitted specimen with addition on Energy Loss analysis of before and after retrofitting work. Furthermore, a crack grading system developed by the Public Work Department (PWD) also had been improved. This grading system will provide ideas and information on how to carry out retrofitting works by using the appropriate repair techniques and at the right time.